Sociodemographic Characteristics of Patients presented with Guillain Barre Syndrome: Experience at Referral Neuroscience Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Guillain Barre Syndrome can occur in different group of people.Objective: The purpose of the present study was to sociodemographic characteristics of patients presented with Guillain Barre Syndrome.Methodology: This cross-sectional study was conducted from October 2017 to September, 2018 in the Department of Clinical Neurology at the National Institute of Neurosciences and Hospital, Dhaka, Bangladesh. The patients were selected according to the selection criteria and after confirmation by electrophysiological study. Details socio-demographic variables of the study population were collected like age, gender, education, occupation, socioeconomic status and so one. Details history and meticulous examination were performed to collect the data according to the variable of interest. All necessary investigations were done at an optimum time. Nerve conduction study and CSF were done after 1st week of onset of the disease in the respective department of the institute.Results: A total number of 108 GBS patients were recruited for this study. Mean age of the study participant was 36.39 ± 16.03 years. Male was predominantly affected with a ratio of male and female in 2.4:1. Maximum patients were in the primary level of education which was 31(28.7%) cases. Highest number of cases were observed in the spring which was 43 (39.8%) cases.Conclusion: In conclusion middle age male patients are most commonly admitted in the hospital presented with GBS which are mostly occurs in Springs.Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):124-129